Diagnostic accuracy of AMH for primary ovarian insufficiency/premature ovarian failure: a real-world cohort study - Mao, Siyu; Yang, Diandian; Wang, Xiaoyun; Cao, Xiaojing (Frontiers in Endocrinology, 2026)
Background/objectivesThe global incidence of Premature Ovarian Insufficiency (POI)/Primary Ovarian Failure (POF) is rising annually, emerging as a critical health threat affecting women of reproductive age. This condition not only induces menopausal-like symptoms but also leads to severe consequences such as infertility, imposing significant physical, familial, and socioeconomic burdens. Given its detrimental impacts, enhancing preventive strategies is imperative. Anti-Müllerian Hormone (AMH), closely associated with ovarian reserve, has gained increasing application in gynecological diagnostics, particularly exhibiting considerable potential in POI/POF evaluation. However, the diagnostic reliability of AMH remains to be fully elucidated. This study aims to rigorously evaluate the diagnostic accuracy of AMH in POI/POF diagnosis, with the goal of improving diagnostic accuracy to facilitate early detection and intervention, thereby providing evidence-based support for POI/POF prevention efforts.MethodsA retrospective analysis was conducted on clinical data from 1,106 reproductive-aged women, divided into three groups: DOR group (n=502), POI group (n=143), and POF group (n=461). Statistical analyses were performed using SPSS 26.0. Comparisons of age, AMH, estradiol (E2), prolactin (PRL), luteinizing hormone (LH), follicle-stimulating hormone (FSH), and progesterone (PRG) were conducted. Significant variables (P<0.05) were included in binary logistic regression models. Receiver operating characteristic (ROC) curves evaluated the diagnostic performance of AMH and its combinations with other parameters.ResultsAge, AMH, E2, PRL, LH, FSH, and PRG differed significantly among groups (P<0.05). For POI, the AUC values for individual markers and their combinations were age (0.494), AMH (0.885), E2(0.757), Age+ AMH (0.888), Age+ E2(0.756), AMH+ E2(0.909), Age+ AMH+ E2(0.910). For POF, the AUC values for individual markers and their combinations were age (0.526), AMH (0.872), E2 (0.803), Age+ AMH (0.877), Age+ E2 (0.805), AMH+ E2 (0.910), Age+ AMH+ E2 (0.912).ConclusionsAMH demonstrates robust diagnostic accuracy for POI/POF diagnosis, with significantly lower levels in affected patients compared to healthy controls. Its diagnostic performance surpasses age and E2, particularly for POF, supporting its utility as a standalone biomarker. These findings advocate for integrating AMH measurement into clinical protocols for early ovarian dysfunction detection in reproductive-aged women.